Mps1 kinase-dependent Sgo2 centromere localisation mediates cohesin protection in mouse oocyte meiosis I - Warif El Yakoubi (Nature Portfolio, 2017)
In meiosis I centromeric cohesin is protected by Sgo2 from Separase-mediated cleavage ensuring that sister chromatids are kept together until their separation in meiosis II. Here the authors demonstrate that Bub1 and Mps1 kinase activities are required for Sgo2 localisation to the centromere region.